Board directorships and carbon emissions: Curvilinear relationships and moderating roles of other board characteristics - Kwok Yip Cheung; Chung Yee Lai (Journal of Risk and Financial Management, 2022)
Our research investigates the moderating roles of various board characteristics (independence, gender diversity, tenure, duality, and size) on the curvilinear relationship between board directorships and carbon emissions using a two-step generalized method of moments (GMM) system approach. We use a total of 1582 observations from 391 firms listed in the US Standard and Poor 500 (S&P 500) index collected from 2015 to 2021. Our findings provide empirical evidence in four aspects: (1) there is a U-shaped curvilinear relationship between board directorships and carbon emissions; (2) board directors should not go over two directorships because carbon emissions are likely to increase; (3) board independence, duality, and size positively moderate curvilinear relationships between board directorships and carbon emissions; and (4) board tenure and gender diversity negatively moderate curvilinear relationships. Our study contributes to expanding the existing literature related to sustainable corporate governance in the US market, and also has implications for regulatory issues, business practice, and further research.
Keywords: 650; corporate governance; board characteristics; carbon emissions